Verder reiken naar genezing: Een theologisch gesprek tussen christenen uit Afrika, de Andes en Nederland - Bom, Klaas (Theologia reformata, 2020)
This article aims to establish an intercultural theological dialogue among African, South American Andes and Dutch perspectives about healing. Part one explores different cultural contexts. Traditional cultures in both African and the Andes contribute to the Christian and integral understandings of healing of the body and mind of the individual, the spiritual and social dimensions, and the material environment. In the Netherlands, however, illness and healing are mainly understood from a modern point of view, one which understands religion and spirituality as strictly private issues that should be separated from public health care. Part two examines three major themes of the intercultural encounter on healing among people from these three contexts: (1) the nature - supernature divide; (2) Divine providence; and, (3) the power of the Holy Spirit.